Effectiveness of PMSE Vat in the New Normal Era in KPP Badan dan Orang Asing (KPP Badora) - Panji Harapan Agung; Endro Andayani; Ratih Kumala (Yayasan Ilomata, 2022)
This study aims to analyze the application of Value Added Tax collection policies on Trading transactions through Electronic Systems at the Corporate and Foreign Tax Service Office. This research is a qualitative descriptive study with data collection techniques through interviews, observations and using written documents. The results showed that the implementation of the VAT collection policy on PMSE, VAT receipts decreased in 2019 due to covid, the number of additional PMSE VAT taxpayers tended to decrease every semester, PSME VAT receipts tended to increase every semester, in terms of the level of effectiveness in 2020, respectively. less effective but in the 2021 period, very effective per semester, the application of the regulations has several weaknesses, namely related to the affirmation of sanctions against collectors who are negligent in carrying out their tax obligations and activities to explore potential Business Actors who are ready to be appointed as PMSE VAT collectors. In addition, public awareness about taxation is still very low, there are still many users who use the service for free and also the prevalence of piracy, this has more or less affected the number of transactions that can be subject to Value Added Tax.